Within-group vocal differentiation of individuals in the cooperatively breeding apostlebird. (9th December 2014) - Warrington, Miyako H.; McDonald, Paul G.; Griffith, Simon C.
Lay Summary: When it comes to helping others, it may pay to be selective, which requires recognizing the difference between individuals or groups of individuals. In apostlebirds, each individual bird has a uniquely distinguishable call, and birds can tell group members apart solely by hearing their voice. Abstract : The ability of animals to discriminate between individuals or groups of individuals (e.g., kin or nonkin) is an important component of many hypotheses proposed to explain the evolution of cooperation and benefits of group living. Previous studies in mammalian systems have demonstrated the use of vocal cues in individual recognition and discrimination. However, there are few such studies in birds. Previous avian studies have largely examined discrimination between different categories of individuals (e.g., mate vs. nonmate, offspring vs. non-offspring) while discrimination between individuals of the same category remain largely unexplored. Previous work has demonstrated that the contact calls of free-living apostlebirds ( Struthidea cinerea ) are individually distinct. Here, we demonstrate that apostlebirds can differentiate between the calls of other individuals of the same social group using vocal cues alone. These findings are biologically relevant as apostlebirds live in complex fission–fusion societies where social groups vary in size, sex ratio, number of breeders, and composition of related and unrelated members.